Centro Direzionale of Naples. A “Smart” Concept - Canfora, Fabrizio; Corbisiero, Fabio (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The topic of urban planning linked to the growth of smart cities is now quite common also in the urban-sociological debate. Recent studies (Besselaar, Koizumi, 2005; Fistola, 2010) identify the main focus of the smart city no longer exclusively in the strategic role played by ICT infrastructures, but above all in the factors enabling urban growth, defined as the ability to stimulate innovative urban developments, along with an increasing attention to the environment, eco-design, improved living levels, as well as the "bio-socio-environmental capital" (Corbisiero, 2013). Based on this theoretical background, the paper highlights the results of a research conducted in Naples on the empirical case of the "Centro Direzionale". It is an intervention of urban design of considerable impact on the city. The design and construction of the Centro Direzionale of Naples is, in fact, an archetype of the smart city; a primal testing of "urban intelligence" in terms of transport systems, infrastructure, logistics, systems for energy efficiency and technology. More generally, a good practice of city administration and of exploitation of strategic spatial planning.